High-pressure high-temperature synthesis and structure of α-tetragonal boron - Evgeny A Ekimov and Igor P Zibrov (Science and Technology of Advanced Materials, 2011)
Microcrystals of α-tetragonal (α-t) boron with unit cell parameters a=9.05077(6) and c=5.13409(6) Å and measured density 2.16–2.22 g cm−3 were obtained by pyrolysis of decaborane B10H14 at pressures of 8–9 GPa and temperatures of 1100–1600 C. The crystal structure is in good agreement with the model proposed by Hoard et al (1958 J. Am. Chem. Soc. 80 4507). However, compared to the original model, we found small deformations of icosahedra and changes in the interatomic